2010
DOI: 10.1177/0734016810379904
|View full text |Cite
|
Sign up to set email alerts
|

Race, Gender, and the Perception of Recently Experiencing Unfair Treatment by the Police: Exploratory Results From an All-Black Sample

Abstract: Using a national poll with a representative sample of Blacks (N ¼ 854), this article examined the experiences of those Blacks who believe that they had recently been treated unfairly by the police. More specifically, the research examined the role of gender in the perception of unfair treatment by the police. The results of the analysis from the full sample found that age (being older), region (being from the South), and being female decreased the likelihood of reporting having been recently treated unfairly b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 66 publications
2
46
0
Order By: Relevance
“…The men and women in the study reported that females were targeted, stopped, and searched less frequently. They were also treated with more leniency than their male counterparts, often escaping detection and/ or arrest (Gabbidon et al, 2011; Steffensmeier & Allan, 1988; Stolzenberg & Alessio, 2004). On the other hand, the men described being the focal point of gang and drug suppression efforts reporting a greater number of stops, searches, and arrests than the women (Durán, 2008; Egley, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The men and women in the study reported that females were targeted, stopped, and searched less frequently. They were also treated with more leniency than their male counterparts, often escaping detection and/ or arrest (Gabbidon et al, 2011; Steffensmeier & Allan, 1988; Stolzenberg & Alessio, 2004). On the other hand, the men described being the focal point of gang and drug suppression efforts reporting a greater number of stops, searches, and arrests than the women (Durán, 2008; Egley, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Women are processed by the criminal justice system at substantially lower rates than men, and although women make up approximately half of the population of the United States, they make up only 23% of arrestees and account for only 7% of incarcerated inmates (Bureau of Justice Statistics (BOJ), 2015). Furthermore, evidence has shown that police are more lenient with female offenders (Gabbidon et al, 2011; Steffensmeier & Allan, 1988; Stolzenberg & Alessio, 2004; Visher, 1983). For example, research has demonstrated that police give fewer citations (Blalock, DeVaro, Leventhal, & Simon, 2007; Engel, Calnon, Liu & Johnson, 2004; Farrell, McDevitt, Bailey, Andresen, & Pierce, 2004) and search and arrest women less frequently (Engel et al, 2004, 2008; Farrell et al, 2004; Novich & Hunt, 2017; Smith, Makarios, & Alpert, 2006).…”
Section: Policing Gangs and Gang Membersmentioning
confidence: 99%
See 2 more Smart Citations
“…Information obtained from interviews or group discussions with participants from different ethnic backgrounds could be valuable in the broader understanding of these findings and in the formulation of interventions and promotion of compliance with the laws and rules set out by the local legal authorities and institutions. It would be also interesting to examine perceptions of the legal system by gender, since some recent work has suggested the existence of differences among men and women in defining their experiences with police (Gabbidon, Higgins, & Potter, 2011).…”
Section: Discussionmentioning
confidence: 99%